The Mediating Role of Organizational Commitment on the Relationship Between Emotional Labor and Work Engagement of Teachers - Sezen-Gultekin, Gozde; Bayrakcı, Mustafa; Limon, İbrahim (Frontiers in Psychology, 2021)
This study aims to investigate the mediating role of organizational commitment on the relationship between emotional labor and work engagement. The study employed a cross-sectional study design. The sample of the study consisted of the teachers working in Sakarya province of Turkey. They participated in the study voluntarily and responded scale items online. The findings showed that teachers’ perceptions of emotional labor, organizational commitment and work engagement Is relatively high. Also, there are statistically significant and positive correlations among variables. On the other hand, the findings confirmed the hypotheses. Teachers emotional labor predicts their organizational commitment and work engagement. Additionally, organizational commitment predicts work engagement and plays a mediating role on the relationship between emotional labor and work engagement. Based on the findings some suggestions were made.